Social Competence in Childhood Brain Tumor Survivors: Feasibility and Preliminary Outcomes of a Peer-Mediated Intervention. Issue 6 (July 2016) - Devine, Katie A.; Bukowski, William M.; Sahler, Olle Jane Z.; Ohman-Strickland, Pamela; Smith, Tristram H.; Lown, E. Anne; Patenaude, Andrea Farkas; Korones, David N.; Noll, Robert B.
ABSTRACT: Objective: Evaluate the acceptability, feasibility, and preliminary outcomes of a peer-mediated intervention to improve social competence of brain tumor survivors and classmates. Method: Twelve childhood brain tumor survivors and 217 classroom peers in intervention (n = 8) or comparison (n = 4) classrooms completed measures of social acceptance and reputation at 2 time points in the year. The intervention (5–8 sessions over 4–6 weeks) taught peer leaders skills for engaging classmates. Individual and classroom outcomes were analyzed with analysis of covariance. Results: Recruitment rates of families of brain tumor survivors (81%) and schools (100%) were adequate. Peer leaders reported satisfaction with the intervention. Preliminary outcome data trended toward some benefit in increasing the number of friend nominations for survivors of brain tumors but no changes in other peer-reported metrics. Preliminary results also suggested some positive effects on classroom levels of victimization and rejection. Conclusion: A peer-mediated intervention was acceptable to families of brain tumor survivors and feasible to implement in schools. Findings warrant a larger trial to evaluate improvements for children with brain tumors and their peers.